Description of the Implementation of Guidance Counseling Management Services - Muhammad Zulfikar; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
Optimization of guidance and counseling services is important so that guidance and counseling services really contribute to the achievement of the Nation or school's vision, mission and objectives. The guidance and counseling service program in schools is unlikely to be achieved if it is not managed in a good quality management. This study aims to describe guidance and counseling management in junior and senior high schools in public and private schools in Jakarta Indonesia. The data obtained can be used as a reference and the basis of plans for improvement and development of guidance and counseling management systems in the school. This research uses descriptive quantitative design with survey method. This study obtained a diverse score on the implementation of the BK management system. In general, the aspects that are quite good are the analysis of the needs when planning the program with the instrument, the making of Satlan, and the division of work tasks. In general, the aspects that need improvement are the addition of BK teachers and skills in using IT.